Molecular characterization of bacterial leaf streak resistance in hard winter wheat - Ramakrishnan, Sai Mukund; Sidhu, Jagdeep Singh; Ali, Shaukat; Kaur, Navjot; Wu, Jixiang; Sehgal, Sunish K. (PeerJ (San Francisco, CA), 2019)
Bacterial leaf streak (BLS) caused by Xanthomonas campestris pv. translucens is one of the major bacterial diseases threatening wheat production in the United States Northern Great Plains (NGP) region. It is a sporadic but widespread wheat disease that can cause significant loss in grain yield and quality. Identification and characterization of genomic regions in wheat that confer resistance to BLS will help track resistance genes/QTLs in future wheat breeding. In this study, we evaluated a hard winter wheat association mapping panel (HWWAMP) containing 299 hard winter wheat lines from the US hard winter wheat growing region for their reactions to BLS. We observed a range of BLS responses among the lines, importantly, we identified ten genotypes that showed a resistant reaction both in greenhouse and field evaluation. Genome-wide association analysis with 15,990 SNPs was conducted using an exponentially compressed mixed linear model. Five genomic regions ( p < 0.001) that regulate the resistance to BLS were identified on chromosomes 1AL, 1BS, 3AL, 4AL, and 7AS. The QTLs Q.bls.sdsu-1AL, Q.bls.sdsu-1BS , Q.bls.sdsu-3AL , Q.bls.sdsu-4AL , and Q.bls.sdsu-7AS explain a total of 42% of the variation. In silico analysis of sequences in the candidate regions on chromosomes 1AL, 1BS, 3AL, 4AL, and 7AS identified 10, 25, 22, eight, and nine genes, respectively with known plant defense-related functions. Comparative analysis with rice showed two syntenic regions in rice that harbor genes for bacterial leaf streak resistance. The ten BLS resistant genotypes and SNP markers linked to the QTLs identified in our study could facilitate breeding for BLS resistance in winter wheat.